Hydrocarbon conversion process improvements - WEISS MICHAEL J; SUN SHOULI; SCHAEFER DIETER J; STUCKY GALEN D; FORD PETER C; SHERMAN JEFFREY H; DOHERTY MICHAEL F; GROSSO PHILIP; RREED ASHLEY W; LORKOVIC IVAN MARC; LAVERMAN LEROY E; MCFARLAND ERIC W (2013)
Improvements in previously disclosed methods of and apparatuses for converting alkanes, alkenes, and aromatics to olefins, alcohols, ethers, and aldehydes includes: safety improvements, use of alternative feedstocks, process simplification, improvements to the halogenation step, improvements to the reproportionation step, improvements to the solid oxide reaction, improvements to solid oxide regeneration, improvements in separations, maintenance, start-up, shut-down, and materials of construction.